Assignments across the Curriculum : A National Study of College Writing - Melzer, Dan (Book collections on Project MUSE., 2014)
In Assignments across the Curriculum, Dan Melzer analyzes the rhetorical features and genres of writing assignments through the writing-to-learn and writing-in-the-disciplines perspectives. Presenting the results of his study of 2,101 writing assignments from undergraduate courses in the natural sciences, social sciences, business, and humanities in 100 postsecondary institutions in the United States, Assignments across the Curriculum is unique in its cross-institutional breadth and its focus on writing assignments. The results provide a panoramic view of college writing.